Kemampuan Representasi Siswa SMP Kelas VIII dalam Menyelesaikan Soal Cerita Materi Peluang Ditinjau dari Gaya Belajar Visual - Fiki Kholilatun; Nizaruddin Nizaruddin; F.X. Didik Purwosetiyono (Perkumpulan Kualitama Edukatika Indonesia, 2023)
This study aims to determine the representational abilities of class VIII junior high school students in solving word problems on opportunity material in terms of student learning styles. This research is a qualitative descriptive study. This research was conducted in class VIII B and VIII E of SMP Miftahul Ulum Boarding School Jogoloyo Demak which were selected based on the results of a questionnaire test. The subjects of this study were selected based on a learning style questionnaire of 60 grade VIII students, 6 students were selected consisting of 2 subjects with a visual learning style, 2 subjects with an auditory learning style, and 2 subjects with a kinesthetic learning style. . The instruments used in this study were a learning style questionnaire test to determine research subjects, math word problems to bring out students' representation abilities, and interview guidelines. The validity of the data uses technical triangulation, namely checking data that has been obtained from the same source using different techniques. The results of the research based on tests and interviews obtained 1) subjects with a visual learning style gave rise to visual representation indicators, and representations of mathematical equations or expressions. 2) subjects with learning styles bring up indicators of visual representation, and representation of equations or mathematical expressions. 3) subjects with kinesthetic learning styles only bring up visual representation indicators.